Integration of Environmental Theology in an Integrative Science Curriculum to Build Ecological Literacy among Muslim Students - Idris Afandi; Muhamad Hanif Fuadi (Institut Bahri Asyiq Galis Bangkalan, 2025)
The global ecological crisis has required a reconstruction of higher education paradigms that extend beyond the cognitive dimension of science to incorporate ethical and spiritual values. In the context of Islamic higher education, students’ ecological literacy has not been systematically developed through an integrative curriculum approach. This study aimed to analyze and synthesize the integration of environmental theology into an integrative science curriculum to foster ecological literacy among Muslim students. The research employed a descriptive qualitative approach using a meta-analytic method based on thematic synthesis of scientific literature published between 2016 and 2025, retrieved from the Scopus, Google Scholar, and Sinta databases. Data were collected through systematic digital documentation and analyzed using content analysis and thematic analysis. The findings indicated that the principles of tawhid, khalifah, amanah, and ecological balance functioned as epistemological foundations in developing an integrative science curriculum. A transdisciplinary integration model strengthened students’ ecological knowledge, religious-ecological attitudes, and critical thinking skills, although the transformation into pro-environmental action required further pedagogical reinforcement. This study contributed to the development of a value-based science curriculum model relevant to Islamic higher education and expanded the discourse on sustainability education from a theological perspective.